2019
DOI: 10.1021/acs.jafc.9b03602
|View full text |Cite
|
Sign up to set email alerts
|

Chlorpyrifos Induces Metabolic Disruption by Altering Levels of Reproductive Hormones

Abstract: Chlorpyrifos (CPF) is a widely used organophosphorus pesticide and detected frequently in fruits, vegetables, as well as in urine and blood in humans. Studies have suggested that CPF can induce metabolic disruption, such as type-2 diabetes mellitus and changed body weight. The main mechanisms are based on oxidative damage, fatty-acid synthesis, and lipid peroxidation. Studies have also shown that CPF can change reproductive hormone (RH) levels. CPF might result in metabolic disorders through altered RH levels.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 124 publications
0
25
1
1
Order By: Relevance
“…CPF, a typical diethylphosphate, is widely used as an insecticide in agriculture, accounting for 68% of the total current-use pesticides in China (Li et al 2014). The extensive application of CPF has resulted in environmental contamination, and it has been detected frequently in FV; 3,5,6-trichloro-2pyridinol (TCPY), a metabolite of CPF, was detected in human urine and blood (Li et al 2019;Liu et al 2014). Second, once entering the human body, OP can be enzymatically converted to their highly toxic oxon forms, which then react with available body cholinesterase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CPF, a typical diethylphosphate, is widely used as an insecticide in agriculture, accounting for 68% of the total current-use pesticides in China (Li et al 2014). The extensive application of CPF has resulted in environmental contamination, and it has been detected frequently in FV; 3,5,6-trichloro-2pyridinol (TCPY), a metabolite of CPF, was detected in human urine and blood (Li et al 2019;Liu et al 2014). Second, once entering the human body, OP can be enzymatically converted to their highly toxic oxon forms, which then react with available body cholinesterase.…”
Section: Discussionmentioning
confidence: 99%
“…2014 ). The extensive application of CPF has resulted in environmental contamination, and it has been detected frequently in FV; 3,5,6-trichloro-2-pyridinol (TCPY), a metabolite of CPF, was detected in human urine and blood ( Li et al. 2019 ; Liu et al.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of pesticides exposure on premature thelarche and precocious puberty, due to their endocrine disruptor characteristics, has been considered in some studies. Exposure of female rats to chlorpyrifos, increased LH, FSH and E2 serum levels, possibly due to an effect on anterior pituitary function [12]. Similarly, imidacloprid increased FSH and decreased LH and progesterone serum levels in treated female rats, probably due to an alteration in GnRH release, with consequences on ovary morphology [13].…”
Section: Pesticides and Pubertal Developmentmentioning
confidence: 96%
“…Epidemiological studies have found that pesticide exposure may result in metabolic disorders, infertility, neurological problems, or weak immune system. Insecticides have also been linked to human DNA damage, multiple degenerative diseases, and cancer [3][4][5]. Organophosphates (OPs) are one of the widely used pesticides (more than 50% of world consumption) globally and their use is expected to increase even more in coming years, with the direct consequence of increased health problems [6,7].…”
Section: Introductionmentioning
confidence: 99%